PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS SIMULASI UNTUK PEMBELAJARAN PERAKITAN KOMPUTER DAN INSTALASI SISTEM OPERASI - I Komang Ari Mahendra; I Gede Mahendra Darmawiguna; Made Windu Antara Kesiman (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2014)
The aimed of this research is developing media based on simulation for learnedcomputer assembly and operating system installation. The background of this research, because the limited of the computer when the student were learned about computer assembly and operating system installation. This research was designed by development model of Dick and Carey.The development of instructional media based on simulation consisted of nine stages, those are identifying instructional goal, conducting instructional analysis, identifying entry behavior characteristic, writing performance objectives, developing criterion-referenced test, developing instructional strategy, developing and selecting instruction, designing and developing formative evaluation, and revising instruction.The acted of feasibility of those instructional media was fixed by the specialist and the student through questionnaire. The percentage of feasibility that was gotten by the contents specialist as big as 92,67% included very good criteria, medium specialist 90,00% included very good criteria, personal trials as big as 91,33% included very good criteria, small group trials as big as 92,33% included very good criteria, field trials as big as 90,67% included very good criteria. The result obtained from this research is this media is suitable to support teaching and learning process at schools with limited infrastructure.